2008
DOI: 10.1136/bjo.2007.136390
|View full text |Cite
|
Sign up to set email alerts
|

Drift of ocular alignment following strabismus surgery. Part 1: using fixed scleral sutures

Abstract: Fixed scleral-suture strabismus surgery generally produces a postoperative undercorrection drift, especially following recession surgery, exotropia or overcorrection at the first postoperative week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 8 publications
2
20
1
4
Order By: Relevance
“…In subsequent support of the validity of our analysis, our finding that there was an overall tendency, which was more marked in exotropes, for under-correction or recurrence in cases of subsequent strabismus surgery is in broad agreement with previous studies on post-operative alignment drift. 19,20 These studies demonstrated a mean under-correction drift, which was more significant in exotropes regardless of using fixed 19 or adjustable sutures. 20 The use of free text in HISS allows the inclusion of other relevant information in this data system, which can then be used to supplement the information derived from SMR1.…”
Section: Discussionmentioning
confidence: 95%
“…In subsequent support of the validity of our analysis, our finding that there was an overall tendency, which was more marked in exotropes, for under-correction or recurrence in cases of subsequent strabismus surgery is in broad agreement with previous studies on post-operative alignment drift. 19,20 These studies demonstrated a mean under-correction drift, which was more significant in exotropes regardless of using fixed 19 or adjustable sutures. 20 The use of free text in HISS allows the inclusion of other relevant information in this data system, which can then be used to supplement the information derived from SMR1.…”
Section: Discussionmentioning
confidence: 95%
“…Em estudo publicado recentemente, não foram observadas variações significativas no posicionamento ocular em pacientes submetidos a cirurgias para correção de esotropia (16) , ao contrário do nosso estudo e de diversos outros previamente publicados. Nos pacientes operados para correção de exotropia, estes autores encontraram variações pós-operatórias no sentido exotrópico, o que está de acordo com os outros estudos citados.…”
Section: Discussionunclassified
“…No caso das exotropias, estudos demonstram taxas de insucesso no alinhamento ocular entre 27% e 86% (12)(13)(14)(15)(16)(17) . O estudo das variações no ângulo de posicionamento dos eixos visuais em pacientes que foram submetidos a cirurgias de estrabismo é de suma importância no entendimento de possíveis fatores de risco relacionados a tal ocorrência e poderá auxiliar no desenvolvimento de abordagens terapêuticas que visem prevenir tal ocorrência.…”
Section: Introductionunclassified
“…Residual/recurrent and consecutive exotropia especially tends to worsen over time, particularly in patients who had monofixation before surgery [31 ], and has been a problem with both fixed scleral sutures and adjustable sutures [32,33 ]. The applicability of adjustable sutures continues to be a subject of debate, advocated by some, even in children, but generally less often performed than a decade ago [33 ].…”
Section: Undesirable Alignment Changesmentioning
confidence: 98%